PENGARUH PROSES PRODUKSI DAN PENGENDALIAN MUTU TERHADAP KUALITAS PRODUK PADA PT. MEDAN TROPICAL CANNING & FROZEN INDUSTRIES DI MEDAN - Rabitha, Nurul; Nasution, Umar Hamdan; Rahim, Rani (Universitas Dharmawangsa, 2025)
This study aims to analyze the influence of the production process and quality control on product quality at PT. Medan Tropical Canning & Frozen Industries in Medan. The research uses a quantitative method with data collection techniques including observation, interviews, questionnaires, and documentation. The results show that both the production process and quality control have a positive and significant effect on product quality, both partially and simultaneously. The t-value for the production process (5.991) and quality control (7.923) is greater than the t-table value (1.660), with a significance level of 0.000 < 0.05. The F-value is 162.500, which is greater than the F-table value of 3.09, and the R² value is 0.770, indicating that 77% of the variation in product quality is explained by the two independent variables.